Association of behaviour-related health risk factors with working life expectancy in adults aged ≥ 50 years: findings from the English Longitudinal Study of Ageing and the Finnish Public Sector Study - Heikkilä, Katriina; Singh Chungkham, Holendro; Pentti, Jaana; Ervasti, Jenni; Kivimäki, Mika; Vahtera, Jussi; Stenholm, Sari; Zaninotto, Paola (Springer Nature, 2026)
Background
Behaviour-related health risk factors are associated with an increased risk of early exit from the working life, but their contribution to working life expectancy (WLE) remains unclear. We investigated the associations of obesity, alcohol intake, smoking and low levels of physical activity with WLE among adults aged 50 years and older.
Methods
Individuals working at study baseline with 18 years of follow-up data from the English Longitudinal Study of Ageing (ELSA) (n = 3233) and the Finnish Public Sector study (FPS) were included (n = 65,255). Obesity, alcohol consumption, smoking and low physical activity were self-reported at study baseline. WLE from age 50 to 70 years was estimated using a multi-state modelling, separately for men and women across occupational position categories (low, intermediate and high), with adjustment for age.
Results
Our findings suggest that individuals who were obese, smoked, had low physical activity levels and reported heavy alcohol use (only in FPS) could expect to work fewer years than those who did not have these behaviour-related health risk factors. A higher number of risk factors was associated with shorter WLE across sex and occupational position categories in both studies. The difference in WLEs between those with no behaviour-related health risk factors and those with ≥ 2 risk factors was up to 1.5 years in ELSA and less than 1 year in FPS.
Conclusion
Having multiple behaviour-related health risk factors is linked to shorter WLE after age of 50 years, a difference that may have important economic implications in societies with ageing populations.